Optimization of culturing conditions for toxicity testing with the alga Oophila sp. (Chlorophyceae), an amphibian endosymbiont. (26th September 2014) - Rodríguez‐Gil, José Luis; Brain, Richard; Baxter, Leilan; Ruffell, Sarah; McConkey, Brendan; Solomon, Keith; Hanson, Mark
Abstract Eggs of the yellow‐spotted salamander (Ambystoma maculatum) have a symbiotic relationship with green algae. It has been suggested that contaminants that are preferentially toxic to algae, such as herbicides, may impair the symbiont and, hence, indirectly affect the development of the salamander embryo. To enable testing under near‐standard conditions for first‐tier toxicity screening, the authors isolated the alga from field‐collected eggs and identified conditions providing exponential growth rates in the apparent asexual phase of the alga. This approach provided a uniform, single‐species culture, facilitating assessment of common toxicity end points and comparison of sensitivity relative to other species. Sequencing of the 18s ribosomal DNA indicated that the isolated alga is closely related to the recently described Oophila amblystomatis but is more similar to other known Chlamydomonas species, suggesting possible biogeographical variability in the genetic identity of the algal symbiont. After a tiered approach to culturing method refinement, a modified Bristol's media with 1 mM NH4+ as nitrogen source was found to provide suitable conditions for toxicity testing at 18 °C and 200 µmol m−2 s−1 photosynthetically active radiation (PAR) on a 24‐h light cycle. The validity of the approach was demonstrated with Zn2+ as a reference toxicant. Overall, the present study shows that screening for direct effects of contaminants on the algal symbiont without the presence of the host salamander is possible under certain laboratory conditions. Environ Toxicol Chem 2014;33:2566–2575. © 2014 SETAC